THE DISCRETIZATION OF THE POLARIZED SIGNAL - P. E. Korneev (Научный вестник МГТУ ГА, 2018)
Often, the monitoring systems solution of remote sensing problems, recognition (classification, discrimination) of radar objects using radio polarimetry methods is required in real time mode with the display of the current information on the radar monitor. Monitoring systems can be either stationary (more often terrestrial) or mobile (based on various transport vehicles). When designing such systems, along with ensuring the required speed and performance of the computer, it is also important to ensure the unification of the units and assemblies, the reduction of weight and size characteristics, simplification of the tuning, increase of the operational reliability. In this case, the use of blocks of digital information processing is required. When digitally processing polarized signals, it is necessary to convert the input analog signal to digital form, i.e. to sampled by time and frequency and perform level quantization. The peculiarities of the discretization of the radar polarized signal over time are considered in the article. Analytical expressions for the input polarized signal are derived with considering the geometric parameters of the polarization ellipse. Formulas are given for the in-phase and quadrature components of the polarized signal, for a complex signal envelope. It is alleged that quadrature processing of the polarized signal leads to a decrease in the requirements for analog-to-digital conversion chips due to a significant reduction in the sampling frequency. After the transformations presented in the article, electronic components, which are already in production by Russian companies in the radio electronic industry, can be used in monitoring systems. The transformations of a polarized signal in the time domain described in the article lead to certain transformations in the frequency domain. We are talking about converting the two-side signal spectrum into a one-side spectrum with its transfer to the video frequency region. Such a conversion helps to reduce the sampling rate from gigahertz to megahertz. Analytic expressions in the time domain are accompanied in the article by a graphic interpretation of the signal spectra in the frequency domain. A scheme for demodulating the in-phase and quadrature components of the polarized signal is given. Functional features of filtering units in the scheme are described, the attention of the designers of the digital signal processing systems to the requirements of the Kotel'nikov's sampling theorem is emphasized.